Building a Successful Family Business Board A Guide for Leaders, Directors, and Families - Pendergast, Jennifer M.; Ward, John L.; Pontet, Stephanie Brun de.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2011)
In Building a Successful Family Business Board , the authors show why private firms need the in-depth expertise and objective feedback that a well-chosen board, including qualified independent directors, can provide, and demonstrates how owners and directors can work together to ensure a long and profitable life for the firm.
Keywords: Management; Organization; Leadership; Small business; Entrepreneurship; Family-owned business enterprise; Management; Organization; Business Strategy/Leadership.; Small Business; Entrepreneurship; Family Business